PREFERENCE OF INDONESIAN MUSLIMS INVESTMENT - Vemy Suci Asih; Abdulah Safe'i (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
This study aims to determine the preferences of the Indonesian Muslim community in choosing investments. The object of this research is the preference of Muslims in selecting investments. The method used in this research is descriptive quantitative, with the analysis method being conjoint analysis. Research data is primary data obtained through questionnaires with random sampling. Respondents in the study amounted to 87 Muslim communities in Indonesia. The results of this study indicate that the investment preference of the Indonesian Muslim community is in Islamic institutions. They are not interested in investments managed by conventional institutions. In addition, the results of this study show that the preferences of Indonesian Muslim communities in choosing the type of investment are interested in saving, then investing in gold. People are not interested in investment deposits, mutual funds, and shares.